The Development Instrument of High Order Thinking Skills Assessment for the Elementary Student - Sola, Ermi; Bundu, Patta (PPSDP International Journal of Education, 2023)
The main objective of this research is to provide High Order Thinking Skills (HOTS) instrument assessment at elementary school. The development model used some phases: develop blueprint test, write the item test, verify the item test, tryout 1, analyses/ revision, tryout 2, analyze test result, and finalize the instrument. Analysis technique for content and construct validity using index Grogery formula at ≥ 0,75 index for relevancy (validity). For empirical validity Karl-Pearson correlation formula, and reliability using coefficient α (Cronbach Alpha). The research result shows that HOTS instrument assessment is valid and reliable, so that it can be used in teaching – learning activities to assess HOTS of the students at elementary school.